2020
DOI: 10.1016/j.isci.2020.101577
|View full text |Cite
|
Sign up to set email alerts
|

Playback of Alarm and Appetitive Calls Differentially Impacts Vocal, Heart-Rate, and Motor Response in Rats

Abstract: Summary Our rudimentary knowledge about rat intraspecific vocal system of information exchange is limited by experimental models of communication. Rats emit 50-kHz ultrasonic vocalizations in appetitive states and 22-kHz ones in aversive states. Both affective states influence heart rate. We propose a behavioral model employing exposure to pre-recorded playbacks in home-cage-like conditions. Fifty-kHz playbacks elicited the most vocalizations (>60 calls per minute, mostly of 50-kHz type), increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 62 publications
3
28
0
Order By: Relevance
“…With respect to playback in the first test, SAL-treated rats showed responses to 50-kHz USV playback which, in qualitative terms, are largely similar to those of Experiments 1 and 2, namely increases in proximal zone entries and dwell times. This indicates that the effectiveness of 50-kHz USV playback to elicit approach cannot only be gauged by using a radial maze, but also by the more simplified platform version, where approach is evaluated by analysis of virtual zones in line with a recent report on social approach evoked by playback of 50-kHz USV in a home cage (Olszy nski et al, 2020). Using the platform, we found that HALO partly blocked the approach to presentation of 50-kHz USV, which only led to an increase in proximal zone times but not proximal zone entries.…”
Section: Experiments 3: State-dependencymentioning
confidence: 90%
See 1 more Smart Citation
“…With respect to playback in the first test, SAL-treated rats showed responses to 50-kHz USV playback which, in qualitative terms, are largely similar to those of Experiments 1 and 2, namely increases in proximal zone entries and dwell times. This indicates that the effectiveness of 50-kHz USV playback to elicit approach cannot only be gauged by using a radial maze, but also by the more simplified platform version, where approach is evaluated by analysis of virtual zones in line with a recent report on social approach evoked by playback of 50-kHz USV in a home cage (Olszy nski et al, 2020). Using the platform, we found that HALO partly blocked the approach to presentation of 50-kHz USV, which only led to an increase in proximal zone times but not proximal zone entries.…”
Section: Experiments 3: State-dependencymentioning
confidence: 90%
“…In aversive situations, such as predator exposure, 22-kHz USV occur, which probably express distress and serve as alarm signals to others (e.g. Blanchard et al, 1991;Fendt et al, 2018;Olszy nski et al, 2020). In appetitive situations, for example roughand-tumble play or mating, 50-kHz USV are emitted (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although initial recordings of heart rate during the playback of ultrasonic calls did not detect changes in heart rate [ 211 ], more detailed and frequent sampling of heart rate detected changes caused by the playback. It is interesting that receivers of the ultrasonic calls develop relevant emotional arousal with autonomic changes [ 212 ]. Playback of 22 kHz vocalizations decreased heart rate in the receiver rats, while the playback of 50 kHz calls increased the rats’ heart rate.…”
Section: Evolution and Functions Of Rat Vocalizationsmentioning
confidence: 99%
“…Playback of 22 kHz vocalizations decreased heart rate in the receiver rats, while the playback of 50 kHz calls increased the rats’ heart rate. These effects were stronger in singly housed rats as compared to pair-housed rats [ 212 ].…”
Section: Evolution and Functions Of Rat Vocalizationsmentioning
confidence: 99%
“…We recently discovered changes in locomotion, USV emission, and HR in Wistar rats exposed to ultrasonic playback from a speaker [26]. In particular, 50-kHz playback elicited abundant appetitive vocalization, increased HR, and locomotor activity.…”
Section: Introductionmentioning
confidence: 99%